Convexity and Spirallikeness Conditions for Two New General Integral Operators - H. Özlem Güney; Serap Bulut (Journal of Mathematics)
We define two new general integral operators for certain analytic functions in the unit disc and give some sufficient conditions for these integral operators on some subclasses of analytic functions.